ACCEPTANCE OF MINI BLACK PIE SUBSTITUTION BLAC RICE FLOUR - Fitri Rahmawati, Ary Dwi Astuti (Prosiding Pendidikan Teknik Boga Busana, 2020)
Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat Wheat is a subtropical plant difficult to grow in Indonesia. The main factors that constrain wheat cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on cultivation in Indonesia is the air temperature and rainfall. The use of excessive grain causes dependence on imports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Orimports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Or imports from other countries. Black rice (Or imports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Orimports from other countries. Black rice (Or imports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Or imports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Orimports from other countries. Black rice (Or imports from other countries. Black rice (Orimports from other countries. Black rice (Or yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. yza sativa L.) is one of the cereals were easily found in Indonesia. The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than The climate is suitable for growing black rice bubidaya facilitate mass. Black contains nutrients better than white rice and brown ricwhite rice and brown ricwhite rice and brown ric white rice and brown ricwhite rice and brown ric white rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ricwhite rice and brown ric e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to e. This study aims to 1to find to findto find to find pie product recippie product recippie product recip pie product recippie product recippie product recippie product recippie product recippie product recip pie product recippie product recip pie product recip e substitutions blace substitutions blace substitutions blace substitutions blace substitutions blace substitutions blace substitutions blac e substitutions blac e substitutions blace substitutions blace substitutions blace substitutions blace substitutions blac e substitutions black rice flour, k rice flour, k rice flour, k rice flour, k rice flour, k rice flour, k rice flour, k rice flour, 2get get get information from information from information frominformation from information from information frominformation frominformation from information frominformation from community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution community acceptance of the product pie substitution of black rice flour, 3 findof black rice flour, 3 find of black rice flour, 3 findof black rice flour, 3 find of black rice flour, 3 find of black rice flour, 3 findof black rice flour, 3 findof black rice flour, 3 find of black rice flour, 3 findof black rice flour, 3 find of black rice flour, 3 findof black rice flour, 3 findof black rice flour, 3 findof black rice flour, 3 findof black rice flour, 3 findof black rice flour, 3 findof black rice flour, 3 find of black rice flour, 3 find sustitusi sustitusi sustitusi sustitusi sustitusi sustitusi nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (definenutrient content in black rice pie. The method used is the Research and Development with 4D model (define nutrient content in black rice pie. The method used is the Research and Development with 4D model (define, design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black design, develop, disseminate). In this study, pie products with the name Mini Black Pie substituted black rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced rice flour as much 0%, 25%, 30% and 35%. Fill pie which is generally a fla sliced fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be fresh fruit will be replaced with a cake. The test rreplaced with a cake. The test r replaced with a cake. The test r replaced with a cake. The test r replaced with a cake. The test rreplaced with a cake. The test rreplaced with a cake. The test rreplaced with a cake. The test r replaced with a cake. The test rreplaced with a cake. The test rreplaced with a cake. The test rreplaced with a cake. The test r replaced with a cake. The test r replaced with a cake. The test rreplaced with a cake. The test rreplaced with a cake. The test r replaced with a cake. The test r replaced with a cake. The test r replaced with a cake. The test r replaced with a cake. The test results showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by esults showed that the pie with 35% substitution can be well received by community. community. community.community. community. KeywordsKeywords KeywordsKeywordsKeywordsKeywordsKeywords: Black riceBlack rice Black rice Black riceBlack riceBlack rice , black rice flour, pieblack rice flour, pie black rice flour, pie black rice flour, pieblack rice flour, pieblack rice flour, pie black rice flour, pie black rice flour, pieblack rice flour, pieblack rice flour, pieblack rice flour, pieblack rice flour, pieblack